Impact of personality influencers on psychological paradigms: An empirical-discourse of big five framework and impulsive buying behaviour - Shakeel Ahmad Sofi; Shabir Ahmad Najar (European Research on Management and Business Economics (ERMBE), 2018)
The main aim of this research was to examine the effect of intrinsic attributes on impulsive buying behaviour among young consumers. Both exploratory and descriptive designs were employed to study the problem in holistic manner. Based on certain parameters, a sample size of 638 was chosen randomly and the study was conducted through a valid and reliable instrument. After employing Exploratory and Confirmatory Factor Analysis on select consumers under the study, results showed that Personality significantly shapes impulsive buying predispositions. In the current study, some of the select personality attributes comprising of Expressive Propensity, Pleasure Seeking Propensity and Sociableness have been found to have positive effect on impulsiveness while as other factors viz. Emotional Stability, Conscientiousness and Conserving Propensity have negative effect on the impulsive buying tendencies. These findings are paramount both from the perspective of consumer welfare advocates and corporates and could largely support them in their respective endeavours.
Keywords: L67; L68; M00; M30; 650; Personality; Impetuous influence; Impulsive buying; Multi group analysis